Análisis preliminar de la vulnerabilidad económica de la ciudad de Cartago, a causa de los efectos de una avalancha que transite por el río Reventado, Costa Rica - Mora C., Sergio (2011)
In this study, a preliminary approach has been carried in order to consider the economic vulnerability of the city of Cartago, Costa Rica. A possible laharic or debris flow has been considered as the threatening scenario. Historic and pre-historic evidences show this to be possible either by a violent triggering of a major active or recently active landslide, particularly San Blás, which is the most active at present, seismic or volcanic activity as well as the development of a high intensity rainfall. All this phenomena could ad alone or combined. Present land use has significantly contributed to increase the hazard, specially the uncontrolled activity of quarries exploiting materials for construction. Damages (direct costs) have been considered as likely to be generated in power lines, oil pipe line, roads, bridges, railroad, aqueducts, housing, industrial parc, population and the early silting of a hydroelectric reservoir. This study must not be considered as exhaustive because of lack of further reliable data about the situation of other industries, commercial buildings and the impact over the gross national product.